Understanding Replication: Trust But Verify. Issue 4 (November 2019) - Suter, W. Newton; Suter, Paula M.
Replication as a pillar of science is described in the context of the replication crisis that first struck psychology but spread quickly to other science-based fields. Empirical evidence suggests that the crisis is real but not well understood. We explain why replication often fails in science and how research in home health can be strengthened by a greater understanding of the value of replication and current thinking about replication success or failure decisions. We conclude with a call for replication in home health nursing that couples original research and replication in the same report.